Radial artery calcification is a predictor of aortic stenosis development and progression after initiation of hemodialysis - Takuya Maeda; Junichiro Nakata; Shuko Nojiri; Toshiki Kano; Haruna Fukuzaki; Kai Suzuki; Hiroaki Io; Yusuke Suzuki (Scientific Reports)
Abstract Aortic stenosis (AS) is an important prognostic cardiovascular disease. However, there are few reports investigating the factors contributing to AS progression in patients with hemodialysis (HD). Because human arterial tissue can be easily harvested during arteriovenous fistula (AVF) surgery, we focused on the association between arterial calcification and AS progression. This is the first study with the aimed to establish a link between radial artery calcification (RAC) level and AS progression in patients with end-stage kidney disease (ESKD). All segments of the radial artery were collected during AVF surgery and stained with the Von Kossa stain. Changes in peak flow velocity (ΔVmax) were calculated based on two echocardiographic findings, and the relationship between RAC level and ΔVmax was analyzed. In the univariate analysis, RAC level, baseline peak aortic jet velocity (Vmax), and age were found to contribute to ΔVmax. After adjusting for age, sex, presence of diabetes, and Vmax at HD initiation, RAC level emerged as an independent factor contributing to ΔVmax. In conclusion, a high RAC level may be a predictor of subsequent development and progression of AS after HD initiation. Our findings may help identify this high-risk group and provide targeted healthcare interventions.